Identifying appropriate service recovery strategies in the event of a natural disaster. (March 2021) - Demeter, Csilla; Walters, Gabrielle; Mair, Judith
Abstract: Purpose: This study examined tourists' reactions to a hypothetical service failure, to better understand how tourists' cognitive and emotional evaluations affect their overall assessments of a service organisation in the aftermath of a natural disaster. Design: A quantitative (n = 414) between subjects' factorial experimental design experiment was conducted. The experiment contained four conditions that aligned with the four different service recovery strategies identified in the literature (apology; compensation; assistance; and assistance with compensation). Findings: During a natural disaster, a tourist's appraisal of the situation will be strongly influenced by the service recovery strategy employed by the service provider. The emotional responses triggered by the service recovery strategy will influence the behavioural intention of the tourist, leading to an opportunity for service providers to overcome potential negative emotions and thus reduce unwanted behaviours such as complaining and negative word of mouth. Research implications: The theoretical contribution lies in the application of the Cognitive Appraisal Theory framework to explore tourists' responses to service recovery strategies following a natural disaster. Practical implications: Increased awareness of visitors' cognitive processes enables managers to develop appropriate service recovery strategies to address service failures occurring during a natural disaster. Originality/value: This study marks one of the first attempts to present empirical findings that enhance our understanding of how service recovery strategies influence tourists' behaviour in the aftermath of a natural disaster.